Polylinguism and multiculturalism in the communication and educational space - Tatyana Lipai; Evgeniya Khinevich (Jan Dlugosz University, 2021)
The problems of the relationship between language and society attract the attention of researchers from different countries representing various scientific areas: philosophy, history, biology, linguistics, theology, pedagogy, psychology, etc. This study actualizes the sociological approach to the study of the social determinants of the formation of polylingualism as a means of professional communication. According to the sociological results, about 70% of the world's population, to one degree or another, speaks two or more languages, which imposes additional obligations on workers providing international professional communications (Beacco, 2002). Modern multilingual interaction should not be one-sidedly understood only as a borrowing of professional foreign language terminology. It includes the social background of the linguistic material: traditions, mimic and pantomimic codes, the national picture of the world - and becomes the most important factor in professionalization. Methods of systemic and functional analysis, comparison. generalization and collection of empirical data (expert interviews, content analysis).